A Study of Indonesia Original Brands Financial Performance - Josua Tarigan; Deborah Christine Widjaja; Helene Lydia Egaputri; Jean-Marc Dautrey (Indonesian Journal of Business and Entrepreneurship (IJBE), 2020)
This research aimed at analyzing the influence of Indonesia Original Brand Index (IOB) on financial performance, which is measured by profitability and market value. The data of this research was from companies in various sectors listed in the Indonesia Stock Exchange (IDX) and whose brand appeared on the published index of Indonesia Original Brands of SWA magazine. The final number of samples is 68 firm-years. This research found that customers’ satisfaction can enhance customer loyalty while also significantly improving customer advocacy. However, the performance of the Indonesia Original Brand Index still not significantly impacted financial performance. This issue happened due to the excessive resources of Indonesian companies, which spent on turning customers' loyalty and be advocates for the brand. This unfavorable profitability outcome can also be due to the unique characteristics of Indonesia’s consumer behavior. According to 81% of IOB respondents, Indonesia’s customers prefer to buy things at a low price and economically. With this behavior of seeking the lowest price, it indicates that customers in Indonesia may shift from one brand to other brands to get the best offer available, therefore not resulting in their constant purchase of one specific brand. Keywords: indonesia original brands index, customer loyalty, customer advocacy, profitability, market value